Observational characterization and empirical modeling of global, direct and diffuse solar irradiances at the Peruvian central Andes - Fashé-Raymundo, Octavio; Flores-Rojas, José Luis; Estevan-Arredondo, René; Giráldez-Solano, Lucy; Suárez-Salas, Luis; Sanabria-Pérez, Elias; Karam, Hugo Abi; Silva, Yamina (Frontiers in Earth Science, 2024)
The present study aims to comprehensively assess the solar irradiance patterns in the western zone of the Mantaro Valley, a region of ecological and agricultural significance in the central Peruvian Andes. Leveraging radiation data from the Baseline surface Radiation Network (BSRN) sensors located in the Huancayo Geophysical Observatory (HYGO-12.04°S,75.32°W, 3350 masl) spanning from 2017 to 2022, the research delves into the seasonal variations and trends in surface solar irradiance components. Actually, the study investigates the diurnal and seasonal variations of solar irradiance components, namely diffuse (EDF), direct (EDR), and global (EG) irradiance. Results demonstrate distinct peaks and declines across seasons, with EDR and EDF exhibiting opposing seasonal trends, influencing the overall variability in, EG. Peaks of, EG occurred in spring (3.32 MJ m−2 h−1 at noon), particularly during October (24.14 MJ m-2 day-1), probably associated with biomass-burning periods and heightened aerosol optical depth (AOD). These findings highlight the impact of biomass-burning aerosols on solar radiation dynamics in the region. In general, the seasonal variability of, EG on the HYGO is lower than that observed in other regions of South America at higher latitudes and reach its maximums during spring months. Moreover, the research evaluates various irradiation models to establish correlations between sunshine hours, measured with a solid glass sphere heliograph, and, EG and EDF at different time scales, showing acceptable accuracy to predict. In addition, the sigmoid logistic function emerges as the most effective in correlating the hourly diffuse fraction (KDh) and the hourly clearness index (KTh), showcasing superior performance compared to alternative functions and exhibiting strong statistical significance and providing valuable insights for future solar radiation forecasting and modeling efforts. This study offers valuable insights for solar radiation forecasting and modeling efforts, emphasizing the importance of interdisciplinary research for solar power generation, sustainable development and climate resilience in mountainous regions like the Peruvian Andes.